Podocytes present antigen to activate specific T cell immune responses in inflammatory renal disease. Issue 2 (22nd August 2020) - Li, Shan; Liu, Ying; He, Yueqin; Rong, Weiwei; Zhang, Mingchao; Li, Limin; Liu, Zhihong; Zen, Ke
Abstract: Infiltration of activated T cells into renal tissue plays an essential role in inflammatory nephropathy. However, the mechanism enabling the renal recruitment and activation of T cells remains elusive. Here we report that inflammatory cytokine‐promoted antigen presentation by podocytes is a key for recruiting and activating specific T cells. Our results showed that diabetes‐associated inflammatory cytokines IFNγ and IL‐17 all upregulated expression of MHC‐I, MHC‐II, CD80 and CD86 on the podocyte surface. Both IFNγ and IL‐17 stimulated the uptake and processing of ovalbumin (OVA) by mouse podocytes, resulting in presentation of OVA antigen peptide on the cell surface. OVA antigen presentation by podocytes was also validated using human podocytes. Furthermore, OVA antigen‐presenting mouse podocytes were able to activate OT‐I mouse T cell proliferation and inflammatory cytokine secretion, which in turn caused podocyte injury and apoptosis. Finally, OT‐I mice subjected to direct renal injection of OVA plus IFNγ/IL‐17 but not OVA alone exhibited OVA antigen presentation by podocytes and developed nephropathy in 4 weeks. In conclusion, antigen presentation by podocytes under inflammatory conditions plays an important role in activating T cell immune responses and facilitating immune‐mediated glomerular disease development. © 2020 Pathological Society of Great Britain and Ireland. Published by John Wiley & Sons, Ltd.